Core radiative collapse characterisation and integrated modelling in WEST plasmas. (1st October 2022) - Ostuni, V.; Morales, J.; Artaud, J.-F.; Bourdelle, C.; Manas, P.; Fedorczak, N.; Dumont, R.; Goniche, M.; Maget, P.; Peysson, Y.; the WEST Team
Abstract: In the full tungsten environment of WEST, during its first phase of operation, around 25% of the pulses exhibited a rapid central electron temperature collapse. In its first phase, WEST plasmas were mostly heated by lower hybrid current drive (LHCD) and ion cyclotron resonance heating (ICRH). In this publication, the collapsing pulses are analysed to understand the key actuators at play. Experimentally, an initial slow reduction of central electron temperature due to a density increase is observed, while the central tungsten profile is flat and constant in time. Then, radiative collapse occurs: the core tungsten profile peaks rapidly, at the same time, the central hard x-ray channel measurement decreases indicating a change in core LHCD absorption. Integrated modelling is used to explore the causality chain. To capture the collapse speed, both, tungsten core peaking and reduction of central LHCD absorption are required. When central LHCD power absorption is reduced, core electron and ion temperature profiles flatten which reduces the tungsten neoclassical thermal screening and leads to the observed core tungsten accumulation.